The effect of nurse behavior on patient satisfaction through service quality as an intervention variable in the inpatient room of Shaykh Yusuf Hospital - Tri Wahyudi; Rahma Rahma (Indonesia Accounting Research Journal, 2025)
Background, Caring for nurses is very important for patient satisfaction, this is a measure of the quality of hospital care. The nurses showed me that they provide comfort, attention, care, and maintain health. Meanwhile, the level of patient satisfaction at the Sheikh Yusuf beIum stabiI and beIum hospitals meets the Community Satisfaction Index, because of patient satisfaction, the quality of care is increasing. The purpose of this study is to determine the influence of nurses' caring behavior on patient satisfaction in the quality of health services at Syekh Yusuf Hospital. Methods The type of research used in this study is a quantitative method, which uses a cros sectional study approach. This research was conducted in the Inpatient Room of Sheikh Yusuf Hospital as many as 294 respondents which were determined through the purpose sampling technique. The data in this study were obtained through questionnaires and secondary data from hospitals. The results and conclusions of the study showed that the direct influence between caring behavior variables on service quality was 0.624, while the direct influence between service quality variables on patient satisfaction was 0.115, so the indirect influence between patient centered care variables on patient satisfaction through service quality was 0.072. It is recommended that the Syekh Yusuf Hospital continue to maintain and improve the caring behavior of nurses towards patients, patient satisfaction and the quality of health services.